Positive intervention for depression and teacher-student relationship in Iranian high school girl students with moderate/mild depression: a pilot randomized controlled trial - Ali Taghvaienia; Arash Zonobitabar (BMC, 2020)
Abstract Background Positive intervention (PI) is a modern and therapeutic approach broadly based on the principles of positive psychology (Rashid in J Posit Psychol 1:25-40, 2014). PI effects at schools have received little attention to date. However, since PI offers a focus on the positive aspects of human experience (Seligman and Csikszentmihalyi in Am Psychol 55:5-14, 2000), we hypothesized that it could exert positive changes in the teacher-student relationship (TSR) and depression symptoms. Therefore, the mentioned pilot study conducted in this article aimed at evaluating PI effects on depression and TSR among Iranian high school girl students with moderate/mild depression. Method In this research, 60 eligible female students (aged 15-18) with a Beck Depression Inventory-II (BDI-II) mild-moderate depression diagnosis, were randomly divided into PI (n = 30) and control groups (n = 30) at the time of entering the study and 2 months later following their assessments through the Inventory of TSR (IT-SR) and BDI-II. The intervention group participated in 8-week 2 h group sessions of PI and the control group was evaluated without any intervention. Results The study was completed with a total number of 49 girls [PI group (n = 24), and control group (n = 25)] and everybody participate in 8 sessions. The intervention group was effective on the variables of BDI-II and IT-SR in a way that the involved girls increased their communication (p = 0.001, d = 0.17), trust (p = 0.001 d = 0.14) after PI training and decreased alienation (p = 0.012, d = 0.11) and depression (p = 0.001, d = 0.15) among other high school students. Conclusion This intervention could function as an unspecific component of a stepped care approach for teenage girls suffering from depression. This study recommends more RCT with large sample sizes among high school boys students and follow-up.